Bandung street photography journey - Azman, Mohammad Firdaus; Sulaiman, Mohamad Zaidi; Samsudin, Fahmi; Fiandra, Yosa; Iskandar, Andang (2024)
Bandung, the capital of West Java province in Indonesia, is brimming with historical allure, natural beauty, and arts scene. It is also a paradise for anyone who is passionate about photography because it provides a variety of subjects to photograph, ranging from breathtaking scenery and internationally recognized landmarks to intriguing street life and traditional Sundanese culture.